Perpetual youth and endogenous labour supply: a problem and a possible solution - Guido Ascari; Neil Rankin (European Central Bank (ECB), 2004)
In the “perpetual youth” overlapping-generations model of Blanchard and Yaari, if leisure is a “normal” good then some agents will have negative labour supply. We suggest a solution to this problem by using a modified version of Greenwood, Hercowitz and Huffman's utility function. The modification incorporates real money balances, so that the model may be used to analyse monetary as well as fiscal policy. In a Walrasian version of the economy, we show that increased government debt and increased government spending raise the interest rate and lower output, while an open-market operation to increase the money supply lowers the interest rate and raises output.
Keywords: D91; E63; 330; Blanchard-Yaari overlapping generations; endogenous labour supply